Analisis Kualitas Pelayanan Pengujian Kendaraan Bermotor Di Dinas Perhubungan Kabupaten Pangkep - Amalia, Anita Reski; Razak, Andi Rosdianti; Taufik, Ahmad (Universitas Muhammadiyah Makassar, 2022)
This study purposed to analyze the quality of motor vehicle testing services. This study used qualitative by using direct interviews with reated informants and qualitative discriptive research aimed to provide an overviewbased on phenomena and facts that occured. The results showed that the tangible dimension had not funny met thequality of service in terms of the provision of facilities and the cleanliness of the environment where the vehicle was tested. The dimensions of employee reliability in providing services were good by carrying out predetermined service standards and procedures. From the dimension of responsiveness, employees are responsive to the needs of the community in helping and providing services quickly, precisely, carefully. The service assurance dimension obtained y the community wasin acordance with the cost guarantee because it was in accordance with the cost guarantee because it was regulated in the Pangkep Regency Regional Regulation Number 1 of 2012, but the certainty of time was not certain, there wasa guarantee given regarding the procurement of vehicle test books and from the empathy dimension employess has shown good service quality with provide friendly, sincere, and non-discriminatory service.Keywords: Quality, Service, Vehicle Testing.